2020
DOI: 10.1186/s13018-020-01713-7
|View full text |Cite
|
Sign up to set email alerts
|

Iliotibial band syndrome rehabilitation in female runners: a pilot randomized study

Abstract: Background: Iliotibial band syndrome (ITBS) carries marked morbidity in runners. Its management is not standardized and lacks evidence base. We evaluated the effectiveness of three different exercises programs in reducing ITBS symptoms. Methods: Patients were divided into three equal treatment groups: ITB stretching (group A), conventional exercise (group B), and experimental hip strengthening exercise (group C). Numeric pain rating scale (NPRS; every week), lower extremity functional scale (LEFS; every 2 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 26 publications
0
27
0
4
Order By: Relevance
“…Authors found no statistical differences between the three groups. The subjects who underwent experimental hip strengthening exercises consistently showed improvements in outcome measures, and never scored less than the other two groups (31).…”
Section: Conservative Treatments Of Iliotibial Band Syndromementioning
confidence: 87%
See 2 more Smart Citations
“…Authors found no statistical differences between the three groups. The subjects who underwent experimental hip strengthening exercises consistently showed improvements in outcome measures, and never scored less than the other two groups (31).…”
Section: Conservative Treatments Of Iliotibial Band Syndromementioning
confidence: 87%
“…From the summary of the studies, several treatment modalities used for this pathology have been found, many of which have demonstrated good results for reducing pain and encouraging a return to sports. In particular, the most used treatments were: muscle strengthening of the hip abductor, either as the main intervention (29)(30)(31) or as an integral part of the rehabilitation programme (7,(32)(33)(34), and manual therapy techniques (7,(35)(36)(37). Other types of treatments were: use of shockwave physical therapy (7), correction of running biomechanics through targeted programs (33,38), correction of malfunctioning muscle and joint downstream and upstream of the knee with a multifaceted approach There was a significant decrease in pain scores and in pain during running in both groups, but no significant difference was observed between the 2 groups.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that plank exercises require no special equipment, are safe, and programs including them are effective at improving hip- and trunk-strength measures [ 21 ], they are often included in rehabilitation programs for injured runners [ 14 , 15 , 16 , 17 , 18 ]. However, whether improved plank times are associated with reduced injury risk in cross country and track-and-field runners is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…Trunk muscle endurance exercises, including front and side planks, are often included in rehabilitation programs for common running injuries [ 14 , 15 , 16 , 17 , 18 ], as well as in programs developed to prevent running-related injuries [ 19 , 20 ] or improve performance [ 21 ]. However, the current evidence on their validity as a screening tool for injury risk is inconsistent.…”
Section: Introductionmentioning
confidence: 99%